UTILIZATION OF QUIPPER SCHOOL AS A MEDIA BASED ON INFORMATION TECHNOLOGY IN ISLAMIC RELIGIOUS EDUCATION LEARNING (AT SMA N 1 SIDAREJA CILACAP) - Farid Ibnu Sani; Wasilatur Rizqiyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2022)
The purpose of this study is to reveal how the use of IT-based media, namely Quipper School, is used as a support for learning in this pandemic period, therefore as a teacher who wants to become a professional teacher is required to be able to present creative, innovative, interesting and fun learning models. This study uses a qualitative approach, which is assisted by data collection methods are interviews, observation and documentation. The results of this study reveal that the quipper media used at SMA Negeri 1 Sidareja is very useful in supporting learning during this pandemic.